Can VHF radars at polar latitudes measure mean vertical winds in the presence of PMSE? - Gudadze, Nikoloz; Stober, Gunter; Chau, Jorge L. (Atmospheric Chemistry and Physics, 2019)
Mean vertical velocity measurements obtained from radars at polar latitudes using polar mesosphere summer echoes (PMSEs) as an inert tracer have been considered to be non-representative of the mean vertical winds over the last couple of decades. We used PMSEs observed with the Middle Atmosphere Alomar Radar System (MAARSY) over Andøya, Norway (69.30∘ N, 16.04∘ E), during summers of 2016 and 2017 to derive mean vertical winds in the upper mesosphere. The 3-D vector wind components (zonal, meridional and vertical) are based on a Doppler beam swinging experiment using five beam directions (one vertical and four oblique). The 3-D wind components are computed using a recently developed wind retrieval technique. The method includes full non-linear error propagation, spatial and temporal regularisation, and beam pointing corrections and angular pointing uncertainties. Measurement uncertainties are used as weights to obtain seasonal weighted averages and characterise seasonal mean vertical velocities. Weighted average values of vertical velocities reveal a weak upward behaviour at altitudes ∼84–87 km after eliminating the influence of the speed of falling ice. At the same time, a sharp decrease (increase) in the mean vertical velocities at the lower (upper) edges of the summer mean altitude profile, which are attributed to the sampling issues of the PMSE due to disappearance of the target corresponding to the certain regions of motions and temperatures, prevails. Thus the mean vertical velocities can be biased downwards at the lower edge, and the mean vertical velocities can be biased upwards at the upper edge, while at the main central region the obtained mean vertical velocities are consistent with expected upward values of mean vertical winds after considering ice particle sedimentation.